2022
DOI: 10.3390/jcm11164748
|View full text |Cite
|
Sign up to set email alerts
|

Controversies and Clinical Applications of Non-Invasive Transspinal Magnetic Stimulation: A Critical Review and Exploratory Trial in Hereditary Spastic Paraplegia

Abstract: Magnetic stimulation is a safe, non-invasive diagnostic tool and promising treatment strategy for neurological and psychiatric disorders. Although most studies address transcranial magnetic stimulation, transspinal magnetic stimulation (TsMS) has received recent attention since trials involving invasive spinal cord stimulation showed encouraging results for pain, spasticity, and Parkinson’s disease. While the effects of TsMS on spinal roots is well understood, its mechanism of action on the spinal cord is stil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 57 publications
0
1
0
Order By: Relevance
“…Putative mechanism of TsMS in PD would be similar to SCS, 7 either by direct dorsal column stimulation or by synchronous activation of several tactile afferents, mostly at multiple dorsal roots. 12 Because we defined stimulation intensity by motor root stimulation, intensity might not have been sufficient to properly activate afferents or spinal cord tracts. The selection of the upper thoracic level was inspired by previous invasive SCS studies conducted at this level, which reported improvements in gait and FOG in PD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Putative mechanism of TsMS in PD would be similar to SCS, 7 either by direct dorsal column stimulation or by synchronous activation of several tactile afferents, mostly at multiple dorsal roots. 12 Because we defined stimulation intensity by motor root stimulation, intensity might not have been sufficient to properly activate afferents or spinal cord tracts. The selection of the upper thoracic level was inspired by previous invasive SCS studies conducted at this level, which reported improvements in gait and FOG in PD.…”
Section: Discussionmentioning
confidence: 99%
“…Trans‐spinal magnetic stimulation (TsMS) is an emerging method that can affect spinal circuitry noninvasively and has shown promise in alleviating motor symptoms of PD, with the benefit of safety and cost in comparison to SCS 12 . Following a previous pilot study showing positive effects of TsMS in patients with PD and gait disorders, 13 we report here a phase II clinical trial on the effects of intermittent θ‐burst (iTB) TsMS on gait, balance, and other motor symptoms.…”
mentioning
confidence: 99%
“…In the only open-label pilot available trial, the authors enrolled 3 patients with a definite genetic diagnosis of HSP [ 42 ]. All patients underwent a single session of transspinal magnetic stimulation (TsMS) at the level of the second thoracic vertebra by a continuous theta burst session of a hundred three-pulse bursts at 50 Hz repeated after a 90-min interval using a figure-eight coil and at 100% of the motor threshold.…”
Section: Non-invasive Stimulation Techniquesmentioning
confidence: 99%